Pseudoporfiria induzida pela diálise tratada com N-acetilcisteína oral - Guiotoku, Marcelo Massaki [UNESP]; Pereira, Fabiola de Paula [UNESP]; Miot, Hélio Amante [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Soc Brasileira Dermatologia, 2011)
Pseudoporphyria is a rare bullous dermatosis that clinically and histopathologically is similar to porphyria cutanea tarda. It mainly affects patients with chronic renal failure on peritoneal dialysis or hemodialysis. Medications can also be involved in the etiology. Diagnosis and management of this condition is a challenge for dermatologists. The authors report a case of pseudoporphyria related to dialysis with favorable outcome after the use of oral N-acetylcysteine.

Pseudoporfiria é dermatose bolhosa rara, semelhante clínica e histopatologicamente à porfiria cutânea tardia. Acomete, principalmente, pacientes renais crônicos em diálise peritoneal ou hemodiálise. Medicamentos também podem ser envolvidos na etiologia. O diagnóstico e o manejo desta entidade é um desafio para os dermatologistas. Os autores demonstram um caso de pseudoporfiria, relacionada à diálise, com evolução favorável após o uso de N-acetilcisteína oral.
Pseudoporphyria induced by dialysis treated with oral N-acetylcysteine
Keywords: Acetylcysteine; Dialysis; Porphyrias; Renal dialysis